Heterotopic interstitial pregnancy: A case report - Joy Anderson; Chase Patterson; April Riley (Elsevier, 2018)
Introduction: Before the advent of assisted reproductive technologies, the incidence of heterotopic pregnancy was estimated to be in 1 out of 30,000 pregnancies in the United States. With interstitial pregnancy comprising only 2.4% of ectopic pregnancies, spontaneous heterotopic interstitial pregnancies are exceedingly rare. Case: A 27-year-old pregnant woman (gravida 3 para 1011) with a history of one prior term vaginal delivery and a spontaneous abortion in the first trimester presented to the emergency department with abdominal pain and a positive home pregnancy test. Transvaginal ultrasound confirmed heterotopic pregnancy and she underwent operative management, at which point a ruptured interstitial pregnancy was identified. Conclusion: Heterotopic and interstitial pregnancies are rare and to see them together in a spontaneous pregnancy is virtually unique. The case report describes our management of this rarely seen condition. Keywords: Heterotopic interstitial pregnancy